Comparative evaluation of mono- and polyclonal antibodies used in identification of interferon alpha-2b products - L. A. Gayderova; Yu. N. Lebedeva; T. N. Lobanova; E. A. Lukinova (Биопрепараты: Профилактика, диагностика, лечение)
Quality control of recombinant interferon (rIFN) products with the help of modern analytical methods, including those used for identification, is becoming increasingly relevant nowadays. Identification is especially challenging in the case of Russian rIFN products that contain not only interferon (IFN) alpha-2b, but also other active ingredients and excipients that hinder the use of physical and chemical methods. Manufacturers of such products use IFN neutralization assay with mono- and/or polyclonal antibodies for identification. The aim of the study was to assess the feasibility of using different types of antibodies in the identification test based on neutralization of IFN antiviral activity in IFN alpha-2b products containing other active ingredients and excipients in addition to IFN. Materials and methods: the following materials were used in the study: MDBK cells, vesicular stomatitis virus, samples of IFN alpha-2b products with different composition and by different manufacturers, mono- and polyclonal antibodies by different manufacturers. Identification of rINFs was carried out by a biological method based on neutralization by specific antibodies of IFN ability to suppress the cytopathic effect of the indicator virus in a cell culture using a reference standard for comparison. Results: both polyclonal and monoclonal antibodies were shown to neutralize the activity of the tested IFN alpha-2b substances. Polyclonal antibodies interact with all products containing the same active ingredients, irrespective of their composition. Monoclonal antibodies interact selectively with some products. Conclusions: polyclonal antibodies can be used for identification of any product containing IFN alpha-2b. The use of monoclonal antibodies for this purpose is limited and depends on the composition of the product.